KECERDASAN SPIRITUAL DALAM MAJELIS PESONA ILAHI PONOROGO - Inayatussalamah, Iin (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2015)
Abstract: Spiritual Knowledge is an essential part of the teachings atPesonaIlahi Assembly,Joresan-Mlarak, Ponorogo and this determines the assembly to receive tremendous public welcoming. What and how the spiritual knowledge is developed is very interesting to study. Through a qualitative approach, this study aimedat examining more deeply by employing in-depth interviews, observation, and documentation. In analyzing the data, interactive analysis was usedby adopting the concept of Miles and Hibermaninvolving three main stages: data reduction, data display, and conclusion.Â  The results showed: 1). The emergence of the Assembly was determined by two factors: a) Murshid teachers,RomoKyaiLabibHudaf gained the trust fromRosulallah Saw to lead the people (Kholifahfilardi) and b) the emergence of spiritual aridity, growing akhlakulkarimah, making intelligent people spiritually. 2) there were four valuesÂ Â  of spiritual intelligence found: a) unifying motion and oral in the sense of wholeness, b) making a whole of senses in the natural subservience, and c) prioritizing the most important primary, and d) subjecting ideology in ideology. 3). The implementation of the congregation spiritual intelligence can be seen from: a) in a polite language and courteous behavior, b) khusnudzon and Qonaâah, c) subject to and obey the command of Murshid teacher, d) Tafakkur. 4) The contribution given was to foster the potential of spiritual intelligence that came from the human nature itself.Â ØÙØºÙØ±ÙÙÙÙ ÙØ±ÙØ§Ù ÙØ§Ø³Ø±ÙØ¬ ÙÙ â ÙÙÙÙØ¥Ø§ Ø¨Ø°ÙØ¬Ø§ Ø³ÙÙØ¬ â ÙÙÙØ¹Øª ÙÙ ÙÙÙ Ø¡Ø²Ø¬ Ø©ÙÙÙØ¹ÙÙØ§ Ø©ÙØÙØ±ÙØ§ ÙØ±Ø§Ø¹ÙÙØ§ ÙØ¥Â Ø¨Ø§Ù Ø°Ø¬ Ø±ÙØ£ ÙÙÙØ§Ø¹ØªÙØ§ ÙØ°Ù ÙÙÙ ÙÙÙ Øª ÙÙÙÙ ÙÙÙØ§Ø¹ØªÙØ§ ÙØ°Ù ÙÙ Ø§Ù .Ø³ÙÙÙØ¬Ø§ Ø§Ø°Ù Ø¯ÙØ¬Ù Ø¹ÙØªÙÙØ¬Ø§ ÙÙ ÙØ±Ø«Ù Ø¨Ø§Ø¬ØªØ³Ø§ Ø§Ø°ÙØ¨ÙÂ ØØ©ÙÙÙØ¹ÙØ§ Ø©ÙØ¨Ø§ÙÙÙØ§ : Ø¨ÙÙØ§Ø³Ø£Ø¨ Ø§ÙÙÙ Ø©ÙÙÙØ¹ÙØ§ Ø©Ø³Ø§Ø±Ø¯ÙØ§Â  â ÙÙÙÙÙØ§ ÙØ®Ø¯ÙÙØ§Ø¨Â  â Ø«ØØ¨ÙØ§ Ø§Ø°Ù ÙÙØ§Ø .ÙÙÙ Ø«ØØ¨ÙÙÂ ÙØ§ÙØ¨Ø±ÙÙ Ø³ÙÙÙ ÙÙÙ Ø¯Ù ÙØ°ÙØ§ Ø¨ÙÙØ³ÙØ£Ø§ â ØªØ§ÙØ§ÙØ¨ÙØ§ ÙÙÙØªØ ÙÙ â Ø«ØØ§Ø¨ÙØ§ ÙØ¯Ø®ØªØ³Ø§ .Ø©Ø¨ÙØªÙÙÙØ§ ÙØ¦Ø§Ø«ÙÙØ§Ù ØØ©Ø¸ØÙØ§ÙÙØ§ÙÂ .Ø«ØØ¨ÙØ§ Ø¬Ø¦Ø§ØªÙ Ø¬Ø§ØªÙØªØ³Ø§ ÙØ« ØØªØ§ÙØ§ÙØ¨ÙØ§ Ø¶Ø±Ø¹Ù ØØªØ§ÙØ§ÙØ¨ÙØ§ Ø¶ÙÙØªØ® :ØªØ§ÙØ·ÙØ®Ø§Ø¨Â ÙÙØ¹ Ø¯Ø´Ø±ÙÙØ§ Ø®ÙØ´ÙØ§ ÙÙØµØ : ÙÙÙØ£Ø§ ØÙÙØ§ÙØ§Ø¹ Ø³ÙÙÙØ¬Ø§ Ø§Ø°Ù Ø±ÙÙØ¸ Ø©ÙÙÙØ® ÙØ¥ )1 : ÙÙØ§ØªÙØ§Ù Ø«ØØ¨ÙØ§ Ø¬Ø¦Ø§ØªÙÙÂ ÙØÙØ±ÙØ§ ÙØ§ÙÙØ¬Ø§ Ø©Ø±ÙØ§Ø¸ Ø¡ÙØ´Ù : ÙÙØ§Ø«ÙØ§Ù Ø)Ø¶Ø±ÙØ£Ø§ ÙÙ Ø©ÙÙÙØ®( Ø©ÙÙØ£Ø§ Ø³ÙØ¦Ø± ÙÙÙÙÙ )Ù -Øµ( ÙÙØ³Ø±ÙØ§ ÙÙ Ø©ÙØ§ÙÙØ£Ø§Â : ÙØÙØ±ÙØ§ Ø¡Ø§ÙØ°ÙÙ ÙÙÙ Ø¹Ø¨Ø±Ø£ Ø©Ø«ÙÙ )2 .Ø§Ù ÙØÙØ±Â  Ù ÙÙØ°ÙØ§ ÙØ§Ø³ÙÙØ¥Ø§ ÙÙÙÙØªÙ ØÙÙØ§Ø®ÙØ£Ø§ ÙØ±Ø§ÙÙ Ø©ÙÙÙØªÙ ØØ¹ÙØªÙÙØ¬Ø§ ÙÙÂ ÙÙØ¶ÙØª ØØ«ÙØ§Ø«ÙØ§ ØÙÙØ§Ø¹ÙØ§ Ø¹ÙØ¶Ø® ÙÙ Ø±ÙØ¹Ø´ÙØ§ Ø¯ÙØÙØª ØÙÙØ§Ø«ÙØ§Ù ØØ±ÙØ¹Ø´ÙØ§ Ø©Ø¯ØÙ ÙÙ ÙØ·ÙÙØ§Ù Ø©ÙØ±ÙØØ§ Ø¯ÙØÙØª ØÙÙÙØ£Ø§Â ÙØ¯ÙÂ  Ù ÙØÙØ±ÙØ§ Ø¡Ø§ÙØ°ÙØ§Ù ÙÙÙÙØ§ ÙØ°Ù ÙÙØ¨Ø·Øª Ø§ÙØ£ )3 .ÙÙÙÙØ§ ÙÙ ÙÙÙÙØ§ Ø¹ÙØ¶ØªØ® ØØ¹Ø¨Ø§Ø±ÙØ§ ØØ©ÙØ¶Ø§ÙÙØ§ Ø¡Ø§ÙØ´ÙØ£Ø§ ÙÙ ÙØ¶ÙÙØ£Ø§Â ÙÙØ§Ø®Ø£Ø¨ ÙÙÙÙØ®ØªÙÙ Ø§Ø¨Ø¯Ø£ØªÙ Ø§ÙÙ ÙÙ Ø§ÙØ³Ø Ø§ÙÙØ§Ù ÙÙÙÙØ§Ù ØÙÙÙØ£Ø§ : ÙÙ Ø©Ø±ÙØ§Ø¸Ù Ø³ÙÙÙØ¬Ø§ Ø§Ø°Ù ÙÙØ¥ Ø©Ø¨Ø³ØªÙÙÙØ§ Ø©Ø¹Ø§ÙÙØ¬Ø§Â ÙÙÙØ¯ÙØ§ ÙÙØ³ÙØ§ Ø§ÙØ£ )4 .Ø±Ù ÙÙØªÙØ§ ØØ¹Ø¨Ø§Ø±ÙØ§Ù ØØ¯Ø´Ø±ÙÙØ§ Ø®ÙØ´ÙØ§ Ø©Ø¹Ø§Ø· ØØ«ÙØ§Ø«ÙØ§Ù .Ø©Ø¹Ø§ÙÙÙØ§ÙÂ  Ù ÙØ¸ÙØ§ ÙØ³Ø ØÙÙØ§Ø«ÙØ§Ù .Ø©ÙÙØ±Ù.ÙØ³ÙÙ ÙØ§Ø³ÙÙØ¥Ø§ Ø©Ø±Ø·Ù ÙÙ Ø©ØªØ¬Ø§ÙÙØ§ ÙØÙØ±ÙØ§ Ø¡Ø§ÙØ°ÙØ§ Ø©ÙØ§Ø· Ø©ÙÙÙØª ÙÙ Ø³ÙÙÙØ¬Ø§ Ø§Ø°Ù ÙÙ